Negotiations of gender and property through legal regimes (14th-19th century) stipulating, litigating, mediating - Lanzinger, Margareth 1965-; Maegraith, Christina Janine 1970-; Clementi, Siglinde 1967-; Forster, Ellinor 1970-; Hagen, Christian 1980- (Legal History Library, 2021)
This volume offers a cross-period (14th-19th century) European comparison of different property regimes brought into conversation with inheritance patterns and resulting gender-specific negotiations and conflicts.